Teachers’ evaluation of vocational curriculum for secondary students with intellectual disabilities: An exploratory analysis from Saudi Arabia - Almalky, Hussain A.; Alqahtani, Shaykhah M. (Research in developmental disabilities, 2025)
Students with intellectual disabilities (ID) continue to face significant challenges in transitioning from school to employment. Vocational education plays a critical role in developing workforce skills and promoting independent living. Despite its importance, the effectiveness of vocational education for students with ID in Saudi Arabia has received limited empirical investigation. This study addresses this gap by evaluating the vocational curriculum through Tyler’s Curriculum Evaluation Theory and the Universal Design for Transition framework, aligning with Saudi Arabia’s Vision 2030. This study examined special education teachers’ perceptions of the vocational curriculum’s appropriateness for secondary students with ID in Saudi Arabia. It also explored whether these perceptions differed based on teachers’ qualifications, area of specialization, years of experience, or institutional setting. A structured quantitative survey measured four curriculum domains: presentation style, content relevance, learning activities, and assessment methods. Data from 84 special education teachers in Riyadh were analyzed using descriptive statistics and independent samples t-tests, with effect sizes (Cohen’s d) reported. Reliability was confirmed via Cronbach’s alpha, and content validity was established through expert review. Teachers generally rated the curriculum favorably, particularly regarding presentation style. In contrast, the learning activities domain received lower ratings, indicating limited use of experiential and individualized pedagogical methods. No statistically significant differences emerged across demographic variables, suggesting strong consensus among respondents. These findings underscore the need to strengthen the learning activities domain to better support students’ development of functional skills and transition to employment. Curricular improvements should integrate practical, differentiated instructional strategies aligned with international standards. Such enhancements align with Vision 2030’s goals for inclusive, outcome-focused vocational education. •The study involved 84 educators in Riyadh evaluating the vocational curriculum for students with intellectual disabilities.•Teachers rated the curriculum as highly suitable, particularly in terms of presentation.•Learning activities were identified as the main area needing improvement, especially in accommodating individual differences.•No significant differences in curriculum evaluations were found based on teachers’ backgrounds or institutions.•Recommendations include enhancing individualized learning activities and aligning the curriculum with real-world job skills.